Modification of bladder thermodynamics in stress urinary incontinence patients submitted to trans-obturator tape: A retrospective study based on urodynamic assessment - Lau, Hui-Hsuan; Lai, Cheng-Yuan; Peng, Hsien-Yu; Hsieh, Ming-Chun; Su, Tsung-Hsien; Lee, Jie-Jen; Lin, Tzer-Bin (Frontiers in Bioengineering and Biotechnology, 2022)
Importance: It needs to be clarified whether trans-obturator tape (TOT)-enhanced urethral resistance could impact the voiding function. Objective: Although TOT has been well-recognized for enhancing urethral resistance to restore continence in stress urinary incontinence (SUI) patients, whether the bladder’s voiding functions adapt to the TOT-enhanced resistance has not been adequately investigated. This study thereby aimed to investigate whether TOT impacts the bladder’s thermodynamic efficacy during the voiding phase. Design: A retrospective analysis of urodynamics performed before and after TOT was assessed. Setting: A tertiary referral hospital in Taiwan. Participants: A total of 26 female SUI patients who underwent urodynamic investigations before and after TOT. Main outcomes and measures: The area enclosed by the pressure-volume loop (Apv), which represents the work performed by the bladder during voiding, in a pressure-volume analysis established by plotting the detrusor pressure versus intra-vesical volume was retrospectively analyzed. Paired Student’s t-tests were employed to assess the difference in values before and after the operation. Significance in difference was set at p < 0.05. Results: TOT increased Apv in 20 of 26 (77%) patients and significantly increased the mean Apv compared to the preoperative control (2.17 ± 0.18 and 1.51 ± 0.13 × 103 cmH2O-ml, respectively p < 0.01). TOT also increased the mean urethral resistance (1.03 ± 0.30 vs. 0.29 ± 0.05 cmH2O-sec/ml, p < 0.01) and mean voiding pressure (25.87 ± 1.72 and 19.30 ± 1.98 cmH2O p < 0.01) but did not affect the voided volume and voiding time. Moreover, the TOT-induced Apv increment showed a moderate correlation with the changes in urethral resistance and voiding pressure (both r > 0.5) but no correlation with changes in voided volume or voiding time. It is remarkable that the TOT-induced urethral resistance increment showed a strong correlation with changes in voiding pressure (r > 0.7). Conclusion and Relevance: The bladder enhances thermodynamic efficacy by adapting the voiding mechanism to increased urethral resistance caused by TOT. Further studies with higher case series and longer follow-ups should assess whether this effect could be maintained over time or expire in a functional detrusor decompensation, to define diagnostic criteria that allow therapeutic interventions aimed at its prevention during the follow-up. Clinical Trial Registration: (clinicaltrials.gov), identifier (NCT05255289)